2012
DOI: 10.1007/s00384-012-1544-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of 0.4% glyceryl trinitrate ointment after haemorrhoidectomy: results of a prospective randomised study

Abstract: Introduction Conventional haemorrhoidectomy (CH) is well known to cause significant post-operative pain and delayed return to daily activities. Both surgical wounds and sphincterial apparatus spasms are likely responsible for the pain. In this study, we evaluated the role of glyceryl trinitrate ointment (GTN) in reducing post-operative pain, ameliorating wound healing and recovery after CH. Patients and methods Between 01/08 and 12/11, 203 patients with symptomatic haemorrhoids were enrolled in the study and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…3 During the time period, multiple methods have been incorporated to reduce this pain, including 0,2% Glyceryl Trinitrate (GTN), 0,4% GTN and 2% Lignocaine gel, as the topic of topical application. [4][5] The ointment of glyceryl trinitrate works as an inner anal sphincter dilator whereas 0.2 GTN reduces pain in the first week following operation. 4 Numerous studies have been done on this subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 During the time period, multiple methods have been incorporated to reduce this pain, including 0,2% Glyceryl Trinitrate (GTN), 0,4% GTN and 2% Lignocaine gel, as the topic of topical application. [4][5] The ointment of glyceryl trinitrate works as an inner anal sphincter dilator whereas 0.2 GTN reduces pain in the first week following operation. 4 Numerous studies have been done on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…The group that used GTN experienced a significant reduction in pain for the first few weeks following the operation with the help of the Visual Analog Scale for 7 days of a study of the pain intensity. [5][6] https://doi.org/10.29309/TPMJ/2020. 27.12.4728 Postoperative pain both at rest and during defecation and healing time has been determined to decrease significantly if patients receive postoperative treatment with GTN.…”
Section: Introductionmentioning
confidence: 99%
“…These 12 trials were published between 2001 and 2014 and had sample sizes ranging from 20 to 210 patients. Nine trials recruited patients with third‐ and fourth‐degree hemorrhoid [10, 14, 15, 19, 20, 22–26]. Milligan–Morgan hemorrhoidectomy was performed in the majority of the included trials; Ferguson‐closed hemorrhoidectomy was performed in 2 studies [20, 25], and stapled hemorrhoidectomy was performed in 2 trials [14, 21].…”
Section: Resultsmentioning
confidence: 99%
“…However, this review did not clarify the heterogeneity of the pooled results, which is crucial in the random effects model [13]. Moreover, several RCTs evaluating GTN in pain control after hemorrhoidectomy have been published recently [14, 15]. Therefore, through a systematic review and meta‐analysis of the evidence available to date, we investigated the outcome in patients using GTN topically after hemorrhoidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Glyceryl trinitrate ointment improved wound healing and reduced postoperative pain [28]. A recent randomized trial confirmed these results [29]. However, this benefit was not confirmed after stapled hemorrhoidopexy [30].…”
Section: Complicationsmentioning
confidence: 99%